A review on protein markers of exosome from different bio-resources and the antibodies used for characterization. (2nd October 2019) - Deng, Fengyan; Miller, Josh
ABSTRACT: Exosomes are small membrane vesicles (ranging from 30 nm to 150 nm), secreted by different cell types upon fusion of multivesicular bodies (MVB) to the cell plasma membrane under a variety of normal and pathological conditions. Through transferring their cargos such as proteins, lipids and nucleic acids from donor cells to recipient cells, exosomes play a crucial role in cell-to-cell communication. Due to their presence in most body fluids (such as blood, breast milk, saliva, urine, bile, pancreatic juice, cerebrospinal and peritoneal fluids), and their role in carrying bioactive molecules from the cells of origin, exosomes have attracted great interest in their diagnostic and prognostic value for various diseases and therapeutic approaches. Although a large body of literature has documented the importance of exosomes over the past decade, there is no article systematically summarizing protein markers of exosome from different resources and the antibodies that are suited to characterize exosomes. In this review, we briefly summarize the exosome marker proteins, exosomal biomarkers for different diseases, and the antibodies suitable for different bio-resources exosomes characterization.